The Golem at Large : What You Should Know about Technology. - Collins, Harry (Knjižnica Canto., 1998)
In this follow up to their earlier book, The Golem: What You Should Know About Science, the authors now consider the Golem of technology. Using the same successful format, in a series of case studies they demonstrate that the imperfections in technology are related to the uncertainties in sciences.